Effects of defined mixed-fungi starter cultures on the nutritional profile and sensory attributes of fermented rice wine lees - Bragais, Edward Kevin B.; Medina, Paul Mark B. (Academia Journal of Biology, 2024)
Rice wine (RW) and its fermentation residue, rice wine lees (RWL), are prepared using a traditional starter culture (TSC). The TSC contains a combination of different fungal and bacterial species that are variable in composition. This study evaluated the effects on the nutritional profile and the sensory qualities of RWL using various combinations of these fungal species as starter cultures. We isolated the three most abundant fungal species in TSC and found them to be Rhizopus oryzae (RO), Mucor indicus (MI), and Saccharomyces cerevisiae (SC). Although sensory evaluation revealed that the RWL produced using the RO+SC was the most preferred (n = 30) in color, aroma, sweetness, bitterness, and clarity, no significant differences were observed compared to when RO+MI+SC was used. Moreover, the RO+MI+SC-produced rice wine lees demonstrated the highest nutritional composition in terms of the following: crude protein content (11.12±0.08%), total energy (412.96±0.07 kcal/100 g), essential amino acids, and vitamin content. Hence, the combination of these three fungal species, RO, MI, and SC, as a starter culture in rice wine fermentation gives rise to rice wine lees with higher nutritional value than using the traditional rice wine starter culture.